Amino Acid Profiling and Chemometric Relations of Black Dwarf Honey and Bee Pollen - Sommano, Sarana Rose; Bhat, Farhan M.; Wongkeaw, Malaiporn; Sriwichai, Trid; Sunanta, Piyachat; Chuttong, Bajaree; Burgett, Michael (Frontiers in Nutrition, 2020)
This research reports the characterization of bee pollen of Apis andreniformis colonies on the basis of morphology, proximate composition, the amino acid, and nutritive patterns in relation with their honey. The pollen gains of the sampling colonies revealed variations in their structure, symmetry, and sculpture. The exile surfaces of the pollens showed psilate, scabrate, clavate, and echinate types of morphology. Total amino acid content of black dwarf honeybee collected pollen (150 mg/g) was found significantly higher than that of honey (15 mg/g) from the same colony. Threonine, phenylalanine, and leucine were among the highest essential amino acid types found in the analyzed pollen and honey samples. The proline content in both products was found the lowest comparing to other amino acid types. The moisture content of the honey samples were found to exceed the limit as prescribed by Codex Alimentarius Commission (<20%). The ash content of the analyzed samples was mostly within the limits (<0.6%) prescribed by international norms. The fat content of the pollens varied from 5.01 to 5.05%, and the honey showed zero fat content. The carbohydrate content in the honey samples was found to differ significantly from each other with a maximum content (73.16%), and the lowest carbohydrate content was 67.80%. The pollen and honey samples were found to have positive effect on in vitro digestibility of proteins.